2013
DOI: 10.1007/s10616-013-9594-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective, cytoprotective and antioxidant effects of Oleum cinnamomi on ethanol induced damage

Abstract: Peptic ulcer disease is a gastrointestinal disorder defined by mucosal damage and free oxygen radicals associated with peptic ulcer and gastritis. Cinnamon is a traditional herb used for many diseases and it has also effects as an antioxidant, anti-inflammatory, antispasmodic and anti-ulcerative. Our research is based on oxidative stress and effects of Oleum cinnamomi on stomach, liver and kidney disorders induced by ethanol. In our experiment, 2-3 month old male Sprague-Dawley rats were used. One hour before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…In this study, we showed that allantoin improved gastritis, mucosal thickness, and cell numbers after ethanol-induced gastritis, decreased leukocyte, and vessel numbers and increased the PGE2 and NP-SH levels in the gastric tissue of male rats. Long-term alcohol consumption is considered to be a risk factor for peptic ulcer, and ethanol administration experimentally induces gastritis, mucosal layer hyperemia, mucosal cell loss, and leukocyte infiltration in rats (3,14,18). Our results showed that ethanol decreased the mucosal layer thickness, parietal, and mucosal cell numbers and NP-SH levels, whereas allantoin treatment increased mucosal thickness, parietal, and mucosal cell counts and NP-SH levels.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we showed that allantoin improved gastritis, mucosal thickness, and cell numbers after ethanol-induced gastritis, decreased leukocyte, and vessel numbers and increased the PGE2 and NP-SH levels in the gastric tissue of male rats. Long-term alcohol consumption is considered to be a risk factor for peptic ulcer, and ethanol administration experimentally induces gastritis, mucosal layer hyperemia, mucosal cell loss, and leukocyte infiltration in rats (3,14,18). Our results showed that ethanol decreased the mucosal layer thickness, parietal, and mucosal cell numbers and NP-SH levels, whereas allantoin treatment increased mucosal thickness, parietal, and mucosal cell counts and NP-SH levels.…”
Section: Discussionmentioning
confidence: 50%
“…The imbalance between gastroduodenal mucosal defenses and counteract aggressive forces are supposed to play an important role in the causation of peptic ulcer [52,53]. Several models mimicking gastroduodenal ulcer have been developed and among these models, administration of indomethacin coupled with hypothermic and restraint stress (SGU) which acquired widespread use and is considered by some experts as the gold standard gastroduodenal ulcer animal models [54,15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aqueous extract of Alismatis rhizome has been found to promote diuresis in rats34 and to have the ability to remove urinary calculi in patients with ureter calculi 35. Cortex Cinnamomi has been found to improve renal function effectively in mice 36. Furthermore, the bioactive components or extracts of the Atractylodis macrocephalae rhizome have been reported to enhance immunity in aged rats 37.…”
Section: Discussionmentioning
confidence: 99%